PENGARUH KEGIATAN FINGER PAINTING INTERAKTIF TERHADAP KEMAMPUAN MENGENAL WARNA PADA ANAK USAI 5-6 TAHUN - Zahara Anggraini; Farida Mayar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Color recognition ability is an important aspect of cognitive development that should be stimulated in early childhood. Based on observations conducted at Iqra’ Kindergarten, Padang City, the color recognition ability of children aged 5–6 years had not developed optimally. This study aimed to determine the effect of interactive finger painting activities on the color recognition ability of children aged 5–6 years. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The sample consisted of 20 children, including 10 children in the experimental class and 10 children in the control class. Data were collected through observation and analyzed using the Independent Sample t-test. The results showed that the mean score of color recognition ability in the experimental class increased from 12.0 to 15.6, while the control class increased from 10.3 to 12.2. The hypothesis test yielded a Sig. (2-tailed) value of 0.037 < 0.05. Therefore, interactive finger painting activities have a significant effect on improving the color recognition ability of children aged 5–6 years.